Pokemon adventures. 01 - Kusaka, Hidenori (Viz Media, 2020)
Red is determined to become a better Pokémon trainer, catch as many Pokémon as he can, and battle gym leaders in order to challenge the Pokémon league. But when he is faced with an enemy too powerful to battle on his own, he must team up with Blue and Green to defeat this incomparable foe.